Secondary Narcolepsy as Worsening Sign in a Pediatric Case of Optic Pathway Glioma - Beatrice Laus; Anna Maria Caroleo; Giovanna Stefania Colafati; Andrea Carai; Romina Moavero; Michela Ada Noris Ferilli; Massimiliano Valeriani; Angela Mastronuzzi; Antonella Cacchione (MDPI AG, 2022)
Narcolepsy, a neurologic disorder that leads to excessive daytime sleepiness, may represent a rare consequence of neoplastic lesions involving the sellar/parasellar and hypothalamic regions, the anatomical areas responsible for wakefulness. Optic pathway gliomas represent the most common neoplasm of these regions and present an excellent overall survival, while long-term neurologic impairments, such as visual loss, endocrinopathies, or sleep disorders, are the principal causes of morbidity. In this case report, we describe a non-NF1 patient suffering from a very extensive optical pathway glioma, who several years after the diagnosis in a radiological condition of stable disease, presented with severe narcolepsy, a rare complication, that led to the death of the patient.